Woman with Susanne Wilson - Unknown:::Creator::::::::::::
Photograph shows a woman speaking at a podium with a microphone. She is holding her glasses. Another woman who is probably Suzanne Wilson is standing behind and to the right of her. The front of the podium reads: "Hyatt San Jose" and "YWCA. Twin tribute to women and industry. Twin. San Jose California."